Preparation of Low-cost Adsorbent Based on Mango Leaf (Mangefira Indica L) Biomass for Methylene Blue (MB) Adsorption - Muhammad Miqdam Musawwa; Annisa Fajriati; Imam Sahroni; Ahmad Said (EKSAKTA: Journal of Sciences and Data Analysis, 2022)
Preparation of leaf mango (Mangefira Indica L)-based adsorbent and its evaluation to reduce methylene blue (MB) concentration have been conducted. Two materials: ads-pristine and ads-CTAB which are referred as native leaf mango adsorbent and CTAB modified leaf mango have been prepared in this study. Cetyltrimethylammonium bromide (CTAB) is cationic surfactant usually used to modify and increase the surface area of the adsorbent for a specific purpose. The materials obtained were characterized by the Fourier Transform Infra-Red (FTIR) and the Scanning Electron Microscope (SEM) with general result, there were detected functional groups indicated the active sites on the adsorbent such as -OH, C-O, C=C. Ads-CTAB was specifically characterized with appearing of C-H aliphatic as the tail of CTAB molecule. SEM images show that both materials have roughness surface and irregular cavities. Additional of CTAB on the surface led the more regularly surface. The optimum pH was in basic region (8), while the optimum adsorbent mass and MB concentration are not clearly found due to the chart still increasing. However, the highest qe was found by 0.01 g of ads-pristine and ads-CTAB with the value 967.25 and 950.75 mg g-1 respectively. As the further evaluation, with the 0.5 adsorbent mass it may be applicated on the MB concentration at around 4000 mg L-1. Kinetics model of this adsorption was followed pseudo second order reactions.